Novel deep eutectic solvents and their application in the liquid-liquid extraction of aromatic compounds / Mukhtar A. Kareem Aljadri - Mukhtar A. Kareem, Aljadri (2013)
The thermal cracking of naphtha is a major source of ethylene. It supplies more than half of the demand on ethylene to the industry. Naphtha contains in some cases high concentrations of aromatic hydrocarbons. They were found to be cracking-resistants and thus their existence in naphtha imposes negative effects on the overall process of ethylene production. Their removal from naphtha was achieved by liquid-liquid extraction using sulfolane as extractant. The extraction by sulfolane is not efficient at low concentrations of aromatics. Additionally, sulfolane is applied at high temperatures. Ionic liquids were proposed by different researches to replace sulfolane as extractants to achieve decent extraction for low concentrations of aromatics. However, their application is still limited at elevated temperatures only. Deep eutectic solvents (DESs) are a new group of ionic liquids which have added advantages. In this work, DESs are proposed as extractants for the above mentioned process. They are synthesized using different salts and hydrogen bond donors. Some DESs have viscosities of less than 0.0686 Pa.s at room temperature which allows them to be easily handled. Sixteen DESs out of twenty one synthesized in this work were applied in the extraction. Different systems of aromatics + aliphatics + DESs were studied at various operating conditions. For a ternary system of benzene + hexane + (methyltriphenylphosphonium bromide:ethylene glycol), a high distribution coefficient of more than 2 was achieved in one extraction experiments, with selectivity as high as 98.3 in another experiment. Other ternary systems studied were toluene + heptane + (tetrbutylphosphonium bromide:ethylene glycol), toluene + heptane + (tetrabutylphosphonium bromide:sulfolane), toluene + heptane + (ethyltriphenylphosphonium iodide:ethylene glycol) and toluene + heptane + (ethyltriphenylphosphonium iodide:sulfolane). The distribution coefficients ranged generally between 0.02 and 0.95 while selectivites ranged generally between 1.5 and 65.8. The experimental results were ascertained by two different correlations methods. The regression coefficients were more than 0.9 for many cases. The non-random two liquids (NRTL) activity coefficients model was applied to correlate the experimental data and to estimate the activity coefficients. Calculated and experimental data show very good agreement and the error criterion is less than 10-4. This work shows that DESs have the advantage over conventional extraction solvents for separation of aromatic hydrocarbons due to their ease of synthesis, tunable physical properties and high selectivities in extraction experiments.